Interactive Multimedia Development Based on STEM in Improving Science Learning Outcomes - Liza Ayu Khairani; Ely Djulia; Wawan Bunawan (Randwick International of Education and Linguistics Science Journal, 2023)
This study aims to improve science learning outcomes by using interactive multimedia based on STEM. This research is a research and development research that refers to the Addie development model which consists of 5 stages, namely the Analysis, Design, Development, Implementation, and Evaluation. The Subject. This study was a grade student of SD Negeri 104197 Klambir village during the field trial of the research subject of 30 students. The research design used design one group pretest- posttest. The research instruments used in data collection are observation, interviews, validation questionnaires and tests. Based on the results of research, interactive multimedia based on STEM developed. The results of the field trial phase The effectiveness criteria are achieved with the number of students reaching 28 people in the post-test or around 93,33% with the results of the gain score classified in the "medium" effectiveness criteria with a score of 0.54 so that interactive multimedia based on STEM is effective for use